Atenção Psicossocial e Psicologia: um mapeamento da produção científica - Luzio, Cristina Amélia [UNESP]; Sinibaldi, Bárbara [UNESP] (My University, 2012)
By the end of the 1970´s, begins the Psychiatric Reform Movement, whose development was the beginning of the construction of a new model, here termed Psychosocial Attention, to substitute the traditional psychiatric model. As such, aspires to be a process of paradigm shift and, therefore, requires transformations in the fields: theoretical-conceptual, technical-assistance, legal-political e sociocultural. This qualitative study composes a research which sought to ascertain the scientific production on the topic conducted by psychology, from the implementation of the Brazilian National Health System and the creation of new services to mental health care. In this sense, it proposed to investigate how the papers published in journals of psychology found in the database LILACS, since 1990, contribute to the process of building a new model that actually replace the so-called traditional psychiatric model.

A partir do final da década de 1970, inicia-se o Movimento Reforma Psiquiátrica, cujo desdobramento foi o início do processo de construção de um novo modelo, aqui denominado de Atenção Psicossocial, substitutivo ao Modelo psiquiátrico tradicional. Como tal, aspira ser um processo de mudança paradigmática e, portanto, requer transformações nos campos: teóricoconceitual, técnico-assistencial, jurídico-político e sociocultural (Amarante, 2007). Este estudo, de natureza quanti-qualitativa, compõe uma pesquisa em que se buscou conhecer a produção científica sobre o tema realizada pela psicologia, a partir da implantação do Sistema Único de Saúde (SUS) e da criação de novos serviços de atenção em saúde mental. Nesse sentido, ele se propôs investigar como os trabalhos publicados em periódicos de psicologia encontrados na base de dados da LILACS, a partir de 1990, contribuem para o processo de construção de um novo modelo que de fato substitua o denominado modelo psiquiátrico tradicional.
Psychosocial attention and psychology: a mapping of scientific production
Keywords: Psychology; De-institutionalizing; Mental health; Psychosocial attention; Psicologia; Desinstitucionalização; Saúde mental; Atenção psicossocial